Pengaruh Sektor Pertanian dan Sektor Industri Pengolahan Terhadap Pertumbuhan Ekonomi dalam Persepektif Ekonomi Islam Kabupaten Lampung Selatan Periode 2024 - Sulaiman Sulaiman; Tamyis Tamyis; Lisa Efrina (Sharing: Journal of Islamic Economics Management and Business, 2025)
This study aims to analyze the influence of the agricultural sector and the manufacturing industry sector on economic growth from the perspective of Islamic economics in South Lampung Regency in 2024. The method used is quantitative with a multiple linear regression approach. The data used are secondary data obtained from relevant institutions and processed using SPSS software. Based on the research findings, it can be concluded that both the agricultural sector and the manufacturing industry sector, either partially or simultaneously, have a significant influence on the economic growth of South Lampung Regency in 2024 within the framework of Islamic economic principles. The regression analysis results show that the agricultural sector has a more dominant positive effect compared to the manufacturing industry sector; however, both together are able to explain 65.1% of the variation in regional economic growth. This indicates that regional economic development based on real sectors such as agriculture and manufacturing is in line with Islamic economic principles that emphasize productivity, distributive justice, and sustainability. Furthermore, the results of the classical assumption tests show that the data fulfill the regression validity requirements, namely normality, absence of multicollinearity, heteroscedasticity, and autocorrelation, making the model feasible for use in formulating regional economic development policies. Therefore, strengthening the agricultural and manufacturing sectors becomes a key strategy that not only drives quantitative economic growth but also reflects the values of blessing, public benefit (maslahah), and balance in the perspective of Islamic economics.